Sistem Informasi Pemesanan Makanan Berbasis Web Dengan Framework Codeigniter (Studi Kasus : Warung Sederhana) - Muhammad Septio (Journal of Student Development Informatics Management (JoSDIM), 2022)
Warung Sederhana is a place of business that serves a menu of food and drinks that are sold in general to the public.  All this time the ordering process is done manually, using paper.  From the process can cause some problems, such as service that is too long to wait, errors in ordering and the amount of fees that must be paid customers sometimes not appropriate.  This study aims to provide better service to visitors, efficiency in ordering food and avoid errors in the process of ordering and payment. The result of this final project is a web-based food ordering information system with Codeigniter Framework a simple Warung case study that can process menus, prices, payment processes and booking reports.